2004
DOI: 10.1530/eje.0.1500027
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin administration affects circulating pituitary and gastro-entero-pancreatic hormones in acromegaly

Abstract: Objective: Ghrelin, a gut -brain peptide involved in the control of energy homeostasis, affects anteropituitary and gastro-entero-pancreatic (GEP) hormone secretion in healthy subjects. We aimed to verify whether such hormonal responses are retained in acromegaly, a disease characterized by high GH, subnormal ghrelin and abnormal GEP hormone levels. Design and methods: The effect of ghrelin (3.3 mg/kg given after overnight fasting as an i.v. bolus) on GH, prolactin (PRL), adrenocorticotropin (ACTH), cortisol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The stimulatory effect of ghrelin on PRL secretion in vivo in humans is slight (24,25), in accordance with the previous studies of GHRPs in humans (43).…”
Section: Discussionsupporting
confidence: 91%
“…The stimulatory effect of ghrelin on PRL secretion in vivo in humans is slight (24,25), in accordance with the previous studies of GHRPs in humans (43).…”
Section: Discussionsupporting
confidence: 91%
“…We and others have shown that GHS retain their GH-releasing effect in active acromegaly (19). Ghrelin, the natural ligand of the GHS-R with more potent GH-releasing activity and specificity was found to elicit an increase in GH in newly diagnosed acromegalic patients, and the response was positively correlated with basal IGF-I concentrations (20,21).…”
Section: Discussionmentioning
confidence: 92%
“…Ghrelin, the natural ligand of the GHS-R, has potent GH-releasing activity and specificity. It was found to increase GH release in newly diagnosed acromegalic patients, a response that is positively correlated with basal IGF-I concentrations (20,21). Aimaretti et al have administered ghrelin to patients with isolated severe GH deficiency and have clearly shown that the GH response to ghrelin is severely impaired (22).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin enhances upper gastrointestinal motility and gastric emptying through the vagus nerves [27][28][29]. It has been shown that there is a feedback mechanism between ghrelin, SS, and GH, which might be considered one of the possible reasons for oesophageal motility dysfunction in patients with acromegaly [9,[30][31][32]. Arosio et al indicated that GH stimulates hypothalamic SS production, as found in acromegaly, and that it may influence circulating SS levels, which might play a role in gastrointestinal motility disorders such as prolonged bowel transit in acromegaly patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic intestinal impairment and possible roles of gastrointestinal hormones (e.g. ghrelin) have been postulated to explain the motility dysfunctions [8,9]. However, the influence of acromegaly on gastrointestinal system motility and the pathological mechanisms involved are still not clarified.…”
Section: Prace Oryginalnementioning
confidence: 99%